THEORETICAL AND METHODOLOGICAL FUNDAMENTALS OF ECONOMIC POWER OF INDUSTRIAL ENTERPRISES - G’ayibnazarov Bahodir Karimovich; Jalolov Ilhomjon Isomiddinovich (EPRA International Journal of Economic and Business Review(JEBR), 2022)
The article describes the concepts of potential, economic potential of the enterprise, scientific approaches, definitions, views, concepts of foreign and domestic scientists on their evaluation.